Metodologia para modelagem e análise de transitórios eletromagnéticos de unidades geradoras em sistemas de 525 KV - Lazzari, Eleonora Fripp (2020)
The complexity of electrical systems instigates the need for increasingly complete analysis of elements belonging to the network. With the addition of elements in the system, to optimize the energy services offered, also increase the probabilities of instability. Some typical scenarios in power systems can generate transients to the system, which provide impacts on current and voltage behavior. When considering that not only power transformers are of paramount importance in the context of electrical systems, but also other equipment relevant to their optimal operation, it is proposed to study the electromagnetic transients that occurred in the networks, which subject this equipment to current and voltage disturbances. This sudden oscillation can generate losses to both the transformer and the system in general, therefore, the studies and analyses performed around transients are fundamental. The objective includes an analysis of the impact and behavior of the current in the network that involves the Santo Antonio HPP, Jirau HPP and bipoles subsystem. Thus, a complex power system is modeled, mainly for the details of generating units and transformers used. It is possible to demonstrate a modeling performed in a permanent regime and transient proportion of events in the network. With the aid of the ATPDraw software, a computational tool that allows the modeling and analysis of transient effects, some scenarios are implemented in the high voltage system, considering the connection of the generating units to the transformer. From the proposed methodology, it becomes possible to observe the impact of the behavior of some quantities as current, in addition to analyzing the effects generated on the restrictions of operational limits of voltage and frequency in the wave profile. The allowable capacity of the equipment, as well as the generating capacities of the generating units, are also considered for restrictions.